The Middle Maccabees archaeology, history, and the rise of the Hasmonean Kingdom - Berlin, Andrea M. 1955-; Kosmin, Paul J. 1984- (Atlanta SBL Press, 2021)
Cover -- Contents -- Abbreviations -- Figures -- The Middle Maccabees -- Part 1. Material Evidence -- The Regions and Material Evidence -- Jerusalem in the Early Hellenistic Period -- Hellenistic Military Architecture from the Giv'ati Parking Lot Excavations, Jerusalem -- Settlement and History of the Northern Judean Hills and Southern Samaria during the Early Hasmonean Period -- Settlements and Borders in the Shephelah from the Fourth to the First Centuries BCE -- Settlement in the Southern Coastal Plain ("Philistia") during the Early Hellenistic Periods (Third through Mid-Second Centuries BCE) -- Go West -- Galilee in the Second Century BCE -- The Upper Galilee and the Northern Coast -- The Hasmonean Settlement in Galilee -- Contribution of the Rhodian Eponyms Amphora Stamps to the History of the Maccabees -- John Hyrcanus I's First Autonomous Coins -- Part 2. The Wider Stage -- Overview -- Before the Spark Ignites the Fire -- Seleucid Throne Wars -- The Machinations of the Ptolemaic State in Its Relationship with Judea (160-104 BCE) -- Silver Coinage in Seleucid Coele Syria and Phoenicia -- Roman Hegemony and the Hasmoneans -- Part 3. Voices -- Reading the Middle Maccabees -- Competitors to Middle Maccabees -- Jewish Voices on Rome and Roman Imperialism -- Conclusion -- Bibliography -- Contributors -- Ancient Sources Index -- Personal Names Index -- Place Names Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Middle East ; Judaea Region; Aufsatzsammlung